PEMBANGUNAN MANUSIA DAN PENCAPAIAN SDGs: PERAN PKK KALURAHAN TIRTONIRMOLO DALAM MEMBERI EDUKASI KESEHATAN IBU DAN ANAK - Hawawi, Alfina (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Human development is an important thing and a process to expand the choices of the Indonesian people. Human development has an orientation to create an environment that allows people to have a better, healthier and more prosperous life. Human development is an aspect that must be considered in achieving the SDGs goals, namely maternal and child health. Tirtonirmolo sub-district is one of the areas that is active in community empowerment programs. The program was implemented through the PKK as an intermediary. PKK provides education related to maternal and child health through posyandu activities and providing nutrition for toddlers, distribution of nutrition for pregnant women, and family planning (KB). This activity is an effort to improve the quality of life and realize the SDGs goals, namely good health and prosperity. This research aims to determine the role of the PKK in providing direction and knowledge about maternal and child health. Apart from that, to find out the contribution to human development and achievement of SDGs, especially in Tirtonirmolo District.